PENGARUH STRUKTUR ASET DAN PROFITABILITAS TERHADAP STRUKTUR MODAL PADA PERUSAHAAN SEKTOR BANGUNAN PROPERTY, REAL ESTATE, AND BUILDING CONSTRUCTION YANG TERDAFTAR DI BURSA EFEK INDONESIA - Julkarnain Julkarnain; Sri Widarti; Eddi Suprayitno (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2022)
The purpose of this study was to determine the effect of asset structure and profitability on the capital structure of property, real estate and building construction companies in 2018-2020. This study uses secondary data in the form of financial statements of companies that are included in the IDX group in 2018-2020.Sampling of this research using purposive sampling and obtained as many as 20 companies. The data collection technique used multiple linear regression test, classical multiple regression assumption test, hypothesis test, and coefficient of determination test. The results of this study indicate that the asset structure has no and significant effect on the capital structure of the property, real estate and building construction companies and profitability and the significant and significant effect on the capital structure of the property, real estate and building construction companies. The percentage of asset structure and profitability variables on capital structure (Debt to Equity Ratio) is 0.241 or about 24.10% while the remaining 75.9 is influenced by other factors not included in this study.